2021
DOI: 10.1016/j.eclinm.2021.100861
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 antibody-positivity protects against reinfection for at least seven months with 95% efficacy

Abstract: Background Reinfection with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been documented, raising public health concerns. SARS-CoV-2 reinfections were assessed in a cohort of antibody-positive persons in Qatar. Methods All SARS-CoV-2 antibody-positive persons from April 16 to December 31, 2020 with a PCR-positive swab ≥14 days after the first-positive antibody test were investigated for evidence of reinfection. Viral genome sequencing was conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
152
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(165 citation statements)
references
References 36 publications
11
152
2
Order By: Relevance
“…Regardless of the basis for any Covid-19 status certificate issued, certification will indicate that the holder has been deemed to pose a lower risk of infection and perhaps transmission of the virus than those without a certificate. At the time of writing, evidence suggests that protection from further infection having had the virus is very high for ~ 7 months [ 68 , 69 ], and that current vaccines can cut household transmission of known variants by half [ 70 ]. Vaccination and prior infection therefore mean risks may indeed be significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the basis for any Covid-19 status certificate issued, certification will indicate that the holder has been deemed to pose a lower risk of infection and perhaps transmission of the virus than those without a certificate. At the time of writing, evidence suggests that protection from further infection having had the virus is very high for ~ 7 months [ 68 , 69 ], and that current vaccines can cut household transmission of known variants by half [ 70 ]. Vaccination and prior infection therefore mean risks may indeed be significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…Within a cohort of over 3.2 million US patients, Harvey et al found a ratio of 0.10 of positive PCRs among those with vs. those without positive antibody test at baseline (for tests performed > 90 days after baseline) [ 8 ]. Among over 43000 people with a positive antibody test (median follow-up 4 months) from Qatar, the estimated efficacy of natural infection against re-infection was above 90% [ 9 ]. Also, data from a population-based study (> 500,000 people) conducted in Denmark suggest that protection after natural SARS-CoV-2 infection was 80% after 6 months (but only 47% for adults aged 65 years or older) [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Key question to address is what level of the neutralizing antibody response could provide protection against infection or reinfection. Several large cohort studies have shown that antibody-mediated immunity could provide strong protection from reinfection in seropositive individuals up to seven months after infection with protection efficacy varied from 80.5% to 95% [48][49][50] . A recent study suggested that the estimated neutralization level for 50% protection against detectable SARS-CoV-2 infection was 20.2% of the mean convalescent level, and the estimated neutralization level required for 50% protection from severe infection was about 3% of the mean convalescent level 51 .…”
Section: Discussionmentioning
confidence: 99%